2020
DOI: 10.1021/acs.macromol.0c01394
|View full text |Cite
|
Sign up to set email alerts
|

Effective Viscosity of Unentangled Random Copolymer Films of Styrene and 4-Methoxystyrene with Different Copolymer Compositions

Abstract: We show that the thickness, h 0 , dependence of the effective viscosity, η eff (h 0 ), of unentangled random copolymer films of styrene (St) and 4-methoxystyrene (MeOS) supported by silica (SiOx) can be easily tuned by tuning the MeOS concentration, X MeOS , in the copolymer. When X MeOS is increased from 0% to 100%, η eff (h 0 ) changes steadily from suppressed to enhanced with decreasing film thickness. At X MeOS = 10%, η eff (h 0 ) displays a nonmonotonic variation. Results obtained by fitting a three-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…With the three mechanosynthesized monomers in hand, preliminary free radical polymerizations (FRPs) were carried out at 70 °C in bulk using azobis­(isobutyronitrile) (AIBN) as an initiator (0.005 mol % with respect to the substrate). Those reactions yielded three polystyrene-type polymers bearing one, two, or three methoxy (MeO) functional groups, respectively, PVMB , PVDMB , and PVTMB . Their number-average molar mass ( M n ), dispersity ( Đ ), glass transition temperature ( T g ), and thermal decomposition temperature ( T d ) are gathered in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the three mechanosynthesized monomers in hand, preliminary free radical polymerizations (FRPs) were carried out at 70 °C in bulk using azobis­(isobutyronitrile) (AIBN) as an initiator (0.005 mol % with respect to the substrate). Those reactions yielded three polystyrene-type polymers bearing one, two, or three methoxy (MeO) functional groups, respectively, PVMB , PVDMB , and PVTMB . Their number-average molar mass ( M n ), dispersity ( Đ ), glass transition temperature ( T g ), and thermal decomposition temperature ( T d ) are gathered in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The past three decades have witnessed intense research focused on nanoscale confinement effects of polymeric glass-formers. Studies have reported that a broad range of properties, including the glass-transition temperature ( T g ), surface viscosity, small-mole...…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experiments have shown that the molecular motions near the surface of polymers and molecular glasses , are faster than those in bulk. Moreover, the enhanced near-surface motions can have a significant impact on the properties of thin polymer films, including their mechanical properties, viscosity, , glass transition temperature ( T g ), dielectric relaxations, thermal expansivity, , and dewetting phenomena. The prevalent model used to describe the thickness ( h ) dependence of the properties of polymer filmsthe layer modelusually assumes that the properties on the film surface do not vary with h. , However, few experiments ,, have investigated whether the surface dynamics is modified when h is decreased below the distance over which enhancement in the near-surface dynamics sustains (ca. 1–1000 nm).…”
Section: Introductionmentioning
confidence: 99%